Effect of He-appm/DPA ratio on the damage microstructure of tungsten. Issue 42 (23rd May 2016) - Harrison, R.W.; Amari, H.; Greaves, G.; Hinks, J.A.; Donnelly, S.E.
Abstract: In-situ ion irradiation and transmission electron microscopy has been used to examine the effects of the He appm to DPA ratio, temperature and dose on the damage structure of tungsten (W). Irradiations were performed with 15 or 60 keV He + ions, achieving He-appm/displacements per atom (DPA) ratios of ∼40, 000 and ∼2000, respectively, at temperatures between 500 and 1000°C to a dose of ∼3 DPA. A high number of small dislocation loops with sizes around 5–20 nm and a He bubble lattice were observed for both He-appm/DPA ratios at 500°C with a bubble size ∼1.5 nm. Using the g.b =0 criterion the loops were characterised as b = ±1/2<111> type. At 750°C bubbles do not form an ordered array and are larger in size compared to the irradiations at 500°C, with a diameter of ∼3 nm. Fewer dislocation loops were observed at this temperature and were also characterised to be b = ±1/2<111> type. At 1000°C, no dislocation loops were observed and bubbles grew as a function of fluence attributed to vacancy mobility being higher and vacancy clusters becoming mobile.